Classification of environmental conditions. Guidance for the correlation and transformation of environmental condition classes of IEC 60721-3 to the environmental tests of IEC 60068. Stationary use at weatherprotected locations Part 4-3, (30th September 2003) - British Standards Institution,
No abstract available